Analisis Program Bantuan Pengembangan Usaha Ekonomi Produktif (PUEP) Bagi Koperasi di Kabupaten Tegal - Oke Setiarso (EKO-REGIONAL, 2008)
This research is proposed to analyze the results of The  Development Programme of  Business Productives to supported the Cooperations Development of Tegal Regency.This analysis shows that of The Development Programme of The business productive of The Cooperations  in generally to influenced financials perspective ,members and  markets servicing perspective  but not to influenced either organization perspective or partnerships perspective of  the Cooperations Development. Key words:       The Development Program of Business Productives, Cooporation, The Cooperations, Development Ladder Assesment (DLA) .